PENGARUH KOMPETENSI, MOTIVASI, DAN ROTASI KERJA TERHADAP KINERJA KARYAWAN DI HOTEL 88 MANGGA BESAR - Etty Nurwati; Febriansyah Ramadhan (Human Capital Development, 2018)
Purpose- This study aims to determine the competency, motivation, work rotation affect partially and simultaneously on employee performance at Hotel 88 Mangga Besar. Design/methology/approach- The population in this study were employees at Hotel 88 Mangga Besar, with samples used in this study as many as 100 people. The sampling technique used is saturated sampling. Data analysis method used in this research is validity test, relicompetency test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test and linearity test). While hypothesis testing includes F test, t test and partial correlation analysis and coefficient of determination (r²). Findings- From the analysis results can be seen that Competency (X1), Motivation (X2), and Work Rotation (X3) has an influence on both partial and simultaneous employee performance.